Generalized self-efficacy of handball players according to playing position in the team - Žakula, G.; Tubic, T.; Jovanovic, S. (SportLogia, 2017)
The aim of this study is to determine statistic significant differences in self-efficacy of handball athletes according to their playing position. The sample consists of 127 handball players from 10 clubs in Serbia, 83 of them are males and 44 are females. All participants are divided in 4 groups (wing, back player, goalkeeper and line player), with an assumption that there are no significant differences between male and female handball players (p= .909). General Self-Efficacy Scale (SGSE; Schwarzer, & Jerusalem, 1981) is applied. Results indicate that there are no significant differences in self-efficacy beliefs in handball players according the playing position in the team (p= .581); handball players on each playing position in the team is equally assured in their skills, regardless the fact that the position activities will affect the outcome of the game. As regards the findings of previous studies and the specificity of handball, this paper provides possible explanation of the obtained results and their implementation in everyday activities of athletes and coaches.